Knowledge gaps in the epidemiology of Toxocara: the enigma remains. Issue 1 (16th December 2015) - HOLLAND, C. V.
SUMMARY: Toxocara species infect a wide range of companion, domestic and wild animals as definitive and paratenic hosts, via multiple routes of transmission, producing long-lived tissue-inhabiting larvae and resistant eggs that can survive in the external environment. Therefore Toxocara and the disease it causes in humans, toxocariasis, represents an ideal aetiological agent for the development of the one health approach. However, despite increasing awareness of the public health significance of toxocariasis, gaps in our understanding of certain key aspects of the parasite's biology and epidemiology remain. These gaps hinder our ability to integrate research effort within the veterinary, medical and environmental disciplines. This review will highlight key deficits in our understanding of nine dimensions of Toxocara epidemiology and discuss a potential scenario to develop a more integrated, one health approach to improve our understanding of the prevention and control of this complex and cryptic zoonosis.